Second‐hand clothing consumption: A generational cohort analysis of the Chinese market. (23rd October 2017) - Liang, Jianfang; Xu, Yingjiao
Abstract: China's rapidly growing economy and consumption are creating serious environmental problems in the country. The throwaway trend credited to fast fashion changes and short‐lived styles made textiles and clothing a new body of solid wastes, resulting in a negative environmental consequence in China. While minimizing consumption of textiles and apparel cannot be the primary solution to environmental problems, it is important to enhance consumer awareness of the impact of their daily consumption on the environment and to promote environmentally sustainable apparel consumption and disposal behaviours. From a generational cohort perspective, this study aims to gain an insight of Chinese consumers' behaviours towards second‐hand clothing, in terms of their consumption intentions and the influence of consumers' perceived values, perceived concerns and descriptive norms on their purchase intentions. Data for this study were collected through a survey of 350 Chinese consumers across the four generational cohorts in China, including the Post‐60s, Post‐70s, Post‐80s and Post‐90s. It was observed that Chinese consumers, in general, had a strong resistance towards second‐hand clothing consumption, with the Post‐70s having the strongest resistance. Significant differences were identified among the four cohorts. The younger generations perceived higher values and held higher purchase intentions than their older counterparts. Different motivations were also identified among the four cohorts in their second‐hand clothing consumption.